EFFICACY AND SAFETY OF LEVETIRACETAM IN CHILDREN WITH ELECTRICAL STATUS EPILEPTICUS DURING SLOW-WAVE SLEEP (ESES) - A. A. Kholin; N. N. Zavadenko; I. D. Fedonyuk; E. S. Il`ina (Эпилепсия и пароксизмальные состояния)
Electrical status epilepticus during slow-wave sleep (ESES) is an EEG pattern of continuous (85-100%) diffuse epileptiform activity in the sleep EEG. The morphology of the epileptiform complexes is identical to benign epileptiform discharges of childhood (BEDC). Epilepsy with ESES (or “Penelope Syndrome”) is a form of age-dependent epileptic encephalopathies with the phenomenon of continuous spike-waves during slow wave sleep. This group of epilepsies also includes Pseudo-Lennox syndrome, Landau-Kleffner syndrome, autistic epileptiform regression and some others. In most cases, the ESES pattern correlates with the severity of cognitive deficit in this population of epileptic children. The aim of this study was to evaluate the efficacy and safety of levetiracetam in children with the ESES pattern in the EEG. Materials and Methods. During the period of 2010-2016, 34 epileptic children with ESES patterns in the EEG (14 boys and 20 girls) treated with levetiracetam (33 in combined and 1 in monotherapy) were studied. Results. Twenty eight of the patients with ESES patterns in the sleep EEG were diagnosed with the ESES form of epilepsy. Among them, 7 idiopathic, 13 symptomatic, and 8 “symptomatic” cases of ESES (the latter resulted from “double pathology” of idiopathic + hypoxic-ischemic factors and these children had cerebral palsy). Among other ESES patients, 3 cases were of Pseudo-Lennox syndrome, 2 cases of Landau-Kleffner syndrome and one girl with autistic epileptiform regression. All 28 children received levetiracetam at therapeutic doses of 20-80 mg/kg/daily. Levetiracetam was highly effective in 67.6% of patients (n=23); of those, 2 children showed full clinical and electroencephalographic remission before reaching puberty, 9 children had clinical remission and 12 children had a significant decrease in seizures and epileptiform discharges. A low efficacy of levetiracetam was seen in 20.6% (n=7) of patients. Disease aggravation (seizures and epileptiform discharges) was found in 11.8% (n=4) of patients. Other negative effects were observed in only 4 (11.8%) children (3 cases of agitation and sleep disturbance and one case of allergic rash). In conclusion, levetiracetam is a highly effective medication (67.6% of cases) in combined antiepileptic therapy in children with ESES. However, the risk of exacerbation was as high as 11.8%. The most effective combinations of levetiracetam were those with valproates and ethosuximide.